Audio Spike Detection on Gamelan using Envelope Shape Pattern Analysis - Solekhan Solekhan; Yoyon K Suprapto; Wirawan Wirawan (Universitas Ahmad Dahlan, 2016)
Spike detection is important for the analysis of gamelan signal processing, in detecting the onset, transcription, and spikes occur on gamelan percussion instruments. Since the current methods: absolute value and NEO, could not detect spikes properly, we proposed to develop a new spike detection method. In this paper, the early stage of spike detection in gamelan music audio was the determination of the peak signal to obtain the form of a signal pattern (envelope like) which was then used as threshold for determining the spike locations. We also demonstrated the effectiveness of their method using shape pattern analysis to detect spikes.